(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the potential of design-based educational technology and examines research conducted by scholars in this field. Additionally, it provides recommendations and suggestions for utilizing design-based educational technology to enhance the creative abilities of "Tarbiya" subject teachers in project development.